DESCRIPTION OF EATING FREQUENCY AND BODY MASS INDEX IN ANEMIC ADOLESCENT GIRLS - Asri Mulawarni; Nunung Siti Sukaesih; Dedah Ningrum (Buletin Veteriner Udayana, 2024)
A common health problem in teenagers is anemia. The need for food intake is very important for the adolescent body because it is for development and growth, and to avoid metabolic disorders. The aim of this study was to determine the description of eating frequency and body mass index in anemia in adolescent girls. This research method uses a descriptive quantitative method, namely by distributing questionnaires, so that you can see a picture of eating frequency based on the results of the questionnaire. To find out body mass index, use body weight in kilograms and height in meters (kg/m²) to calculate it. The results of the research showed that the frequency of eating among young women from 67 respondents showed that the percentage was very good, only 1 respondent (1.4%) and the lowest percentage was not good, 48 respondents (71.6%). For the research results, body mass index had the highest presentation, namely normal, 25 respondents (37.3%). From the results of research at SMPN 3 Sumedang class VII, most of them had a normal body mass index, but the frequency of eating very well was very low. Therefore, it is hoped that efforts can be made to prevent anemia by improving diet.